'There Must Be a Poetry of Sound That None of Us Knows…': Early British documentary film and the prefiguring of musique concrète. Issue 2 (12th July 2017) - Cox, Geoffrey
Abstract : Standard histories of electronic music tend to trace the lineage of musique concrète as lying mainly in the Futurists' declarations of the 1910s, through Cage's 'emancipation' of noise in the 1930s, to Schaeffer's work and codifications of the late 1940s and early 1950s. This article challenges this narrative by drawing attention to the work of filmmakers in the 1930s that foreshadowed the sound experiments of Pierre Schaeffer and thus offers an alternative history of their background. The main focus of the article is on the innovations within documentary film and specifically the sonic explorations in early British documentary that prefigured musique concrète, an area ignored by electronic music studies. The theoretical and philosophical underpinnings of the documentary movement's members, particularly their leader John Grierson, will be compared with those of Pierre Schaeffer, and the important influence of Russian avant-garde filmmaking on the British (and musique concrète) will be addressed. Case studies will focus on the groundbreaking soundtracks of two films made by the General Post Office Film Unit that feature both practical and theoretical correspondences to Schaeffer: 6.30 Collection (1934) and Coal Face (1935). Parallels between the nature and use of technologies and how this affected creative outputs will also be discussed, as will the relationship of the British documentary movement's practice and ideas to post-Schaefferian 'anecdotal music' and the work of Luc Ferrari.